The Effect of YouTube Effectiveness on Community Population Popularity (Video Study of Da'wah Ustadz Abdul Somad, Lc., MA on the Tafaqquh Channel Videos among the Teenagers in the Mosque Teenager Association Agung (IRMA) Palembang) - Vito, Adli Danu; Meilinda, Nurly (Open Access Indonesia Journal of Social Sciences, 2019)
Youtube is one of the mass media types of online media that provides information, knowledge, education and entertainment to a wide audience that has considerable appeal compared to other online media. Therefore, some people can gain popularity through YouTube, in this case Ustadz Abdul Somad, Lc., MA, one of the public figures who gained popularity through YouTube with the publication of his lecture videos. In this study the authors used the theory of effectiveness of mass media by Muhammad Nur Jaya and theory by Rahmat as a benchmark. In the theory of mass media effectiveness there are three dimensions, namely 1) Displaying audio and visuals, 2) Easily accessible, 3) Low cost and popularity theory has three dimensions, including 1) Credibility, 2) Attraction, 3) Power. The results showed that there was a significant influence between the effectiveness of YouTube on the tafaqquh video channel on the popularity of the community leader Ustadz Abdul Somad, Lc., MA among adolescents who were members of the Palembang Grand Mosque Youth Association (IRMA) with a fairly high level of popularity.